135k views
5 votes
Solve the logarithmic equation. Write the answer in exact, simplified form.log (-p) + log 6 = log (7p-26)The solution set is.()

User Glaebhoerl
by
5.6k points

1 Answer

4 votes

We have to solve the logarithmic equation:


\log (-p)+\log 6=\log (7p-26)

We can start by applying the product rule to the terms in the left side:


\begin{gathered} \log (-p)+\log 6=\log (7p-26) \\ \log (-p\cdot6)=\log (7p-26) \end{gathered}

Then, as both sides apply the same logarithm and are the only terms, the arguments of both have to be equal:


\begin{gathered} -p\cdot6=7p-26 \\ -6p=7p-26 \\ -6p-7p=-26 \\ -13p=-26 \\ p=(-26)/(-13) \\ p=2 \end{gathered}

Answer: p = 2

User JDur
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.